The effects of temperature on the dormancy and germination of Cirsium arvense (L.) Scop. seeds - Anna Bochenek; Janusz Gołaszewski; Agnieszka I. Piotrowicz-Cieślak; Ryszard J. Górecki (Acta Societatis Botanicorum Poloniae, 2011)
The ecophysiological regulation of seed dormancy in perennial species and those with a varied life cycle has not been studied in detail yet. That is why an attempt has been made to determine the Cirsium arvense seed water relations during stratification and afterripening at different temperatures and germination at constant or fluctuating temperatures on the basis of the hydrotime model. The obtained results showed that breaking of the primary dormancy of achenes took place only during the first stratification month at moderate temperatures, mainly due to an increase in the average water-stress tolerance in a seed population. The induction of secondary seed dormancy during after-ripening at all temperatures resulted mostly from a substantial loss of the seeds' ability to tolerate water stress. Fluctuating temperatures affected neither seed germination nor the hydrotime model parameters. The analysis of the variations of hydrotime model parameters allows a better understanding of the physiological basis of seed dormancy relief and induction.